2016
DOI: 10.2174/1574892811666151111142721
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives in Engineered Mesenchymal Stem/Stromal Cells Based Anti- Cancer Drug Delivery Systems

Abstract: Understanding and apprehension of the characteristics and circumstances in which mesenchymal stem cells (MSCs) affect and make alterations (enhance or reduce) to the growth of tumors and metastasis spread is pivotal, not only for reaching the possibility to employ MSCs as drug delivery systems, but also for making forward movement in the existing knowledge of involvement of major factors (tumor microenvironment, soluble signaling molecules, etc.) in the process of carcinogenesis. This capability is reliable be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…Two types of cells were used in the experiments: dental pulp stem (DPS) cells and the breast cancer cell line MCF-7. It should be noted that recent studies have shown a great deal of interest in stem cells for the delivery of antitumour drugs [105][106][107][108]. DPS cells were isolated from the third molar germ extracted for orthodontic indications from a healthy, 16-year-old patient.…”
Section: Methodsmentioning
confidence: 99%
“…Two types of cells were used in the experiments: dental pulp stem (DPS) cells and the breast cancer cell line MCF-7. It should be noted that recent studies have shown a great deal of interest in stem cells for the delivery of antitumour drugs [105][106][107][108]. DPS cells were isolated from the third molar germ extracted for orthodontic indications from a healthy, 16-year-old patient.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to their roles in immunoregulation, MSCs are fibroblast-like multipotent cells that have the ability to differentiate into osteoblasts, adipocytes, chondrocytes, and thus a powerful tools for tissue engineering, regenerative medicine and also drug delivery (Pittenger et al, 1999;Gjorgieva et al, 2013;Ackova et al, 2016;Chen et al, 2016). As osteoblast differentiation was not altered in our NOS2 −/− rat BMSCs, we considered that NOS2 may not play an essential role in rat MSC osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the true risk of using ASCs in breast cancer reconstruction is still debatable [15,20]. Nevertheless, there is research being done to mitigate this potential risk by testing ASCs as anti-cancer drug delivery systems [21]. One such study by Scioli et al showed that ASCs can uptake and release the chemotherapeutic agent Paclitaxel (PTX) to suppress CG5 breast cancer cell proliferation and survival both in vitro and in vivo in mice, suggesting that ASCs may have therapeutic potential in suppressing breast cancer recurrence [22].…”
Section: Introductionmentioning
confidence: 99%